Game Edukasi Trash Sorter Untuk Meningkatkan Kesadaran Pemilahan Sampah Berbasis Model Addie - Nugraha, Nur Budi; Santosa, Yaqutina Marjani; Puspaningrum, Alifia (Institut Teknologi Garut, 2025)
The low level of public awareness regarding waste sorting is one of the major contributing factors to flooding in various regions of Indonesia. This condition indicates the need for interactive and engaging learning media to foster environmental awareness from an early age. This study aims to develop the Trash Sorter educational game as a web-based learning medium that introduces waste-sorting concepts within the context of flood-mitigation efforts. The development process followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) systematically. At the implementation stage, the game was tested on 20 participants consisting of elementary school students and community members living in flood-prone areas. Evaluation was conducted through pre-tests and post-tests to measure improvements in user understanding. The results showed an increase in the average score from 56.75 on the pre-test to 87.25 on the post-test. In addition, internal alpha testing successfully fixed several bugs and improved application performance. Thus, Trash Sorter has proven effective as an educational medium for increasing waste-sorting awareness as part of flood-mitigation efforts. Moving forward, the game has the potential to be implemented as environmental education media in elementary schools and community organizations to support learning based on environmental literacy and disaster mitigation.